2007
DOI: 10.1080/14764170701400085
|View full text |Cite
|
Sign up to set email alerts
|

A self‐reported clinical trial investigates the efficacy of 1072 nm light as an anti‐ageing agent

Abstract: Regular application of a non-thermal quantity of 1072nm light around the eyes demonstrated efficacy as an anti-ageing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The potential of inducing beneficial textural and pigmentary changes to sun damaged and aged skin without the need of ablation, will result in dramatically less post‐operative immediate and long‐term undesired effects. Various laser and intense light systems have been used in a non‐ablative approach 7–10. These approaches have resulted in collagen production and subsequent dermal thickening with a reduction of surface textural changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of inducing beneficial textural and pigmentary changes to sun damaged and aged skin without the need of ablation, will result in dramatically less post‐operative immediate and long‐term undesired effects. Various laser and intense light systems have been used in a non‐ablative approach 7–10. These approaches have resulted in collagen production and subsequent dermal thickening with a reduction of surface textural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared non‐ablative systems have included wavelengths at 980, 1,072 7, 1,320 8, 1,450 9, 1,540 nm 10 and IPL broad wavelength emissions 11. The light may be delivered in a homogenous or fractionated pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding control treatments, while most participants received no oral/topical medical treatment or LED light, 6,7,26,28,30,32,33,37,40,[42][43][44][46][47][48][49]51 several studies used a placebo (sham) device for the control arm. 5,27,34,35,[38][39][40][41]45,50 In addition, there were some individual cases using differential control treatments, such as topical 5% benzoyl peroxide, 31 oral famciclovir, 7 0.1% retinol-based cream, 36 and even fractional CO 2 laser. 3 The effectiveness of LED therapy in skin treatment was indicated through the various outcomes, including reduction of inflammatory acne (n = 9), healing time of herpes zoster ophthalmicus/herpes simplex labialis (n = 3), reduction of wrinkle (n = 6), skin wound area (n = 3), psoriasis severity index (n = 3), and erythema index rate (n = 7).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…A total of six studies reported the use of LED in improving skin rejuvenation. 5,[36][37][38][39][40] In which, two RCTs using a red LED irradiation reported that red LED was able to slightly improve the signs of Regarding LED-NIR-based skin treatment, a placebo-control study on 79 patients reported a 32% improvement in skin texture after 8-10 weeks irradiation with LED-NIR. 38 Nikolis et al (2016) reported that blue LED was more effective in reducing signs of wrinkles in 32 patients after a 4-week treatment than topical treatment with a cream containing 0.1% retinol.…”
Section: Skin Rejuvenationmentioning
confidence: 99%
“…Six RCTs used LEDs for skin rejuvenation (2 LED‐RL; 1 LED‐nIR; 1 LED‐BL; 2 LED‐RL and LED‐nIR) . In a RCT of 23 patients, LED‐RL (630‐nm, 80 mW/cm 2 , 96 J/cm 2 , 20 minutes) did not significantly improve skin elasticity or hydration (assessed using cutometers and corneometers) compared to untreated controls after thrice daily treatments for 3 weeks .…”
Section: Fda‐cleared Led Treatments Of Skin Conditionsmentioning
confidence: 99%